Praktyczny wymiar idei oratorium w działalności wychowawczej Rodziny Salezjańskiej w Polsce - Sys, Dorota (Studia Pastoralne, 2026)
The article contains a theoretical study of the idea of the Salesian Oratory based on the quadruple metaphor of oratory as home, school, parish and backyard and empirical verification of its actual application in the educational practice of Salesians Sisters and Salesians Priests in Poland. The result of the analyses are the applications and proposals aimed at pastoral care of fidelity to the original upbringing style of Saint John Bosco, attempt to answer the signs of the times and adapting pastoral and educational activities to the needs of today’s youth.